A novel nonlinear large‐signal statistical model of GaN HEMT used in S‐band power amplifier design and yield estimation. (22nd March 2016) - Chen, Zhikai; Xu, Yuehang; Wang, Changsi; Wen, Zhang; Rong, Chuicai; Xu, Ruimin
Summary: A novel GaN high‐electron mobility transistor (HEMT) nonlinear large‐signal statistical model based on empirical equivalent circuit is proposed in this paper. Thirty‐four GaN HEMTs from 10 batches are measured, and all the parameters of the large‐signal model are extracted by in‐house parameter extraction program. We choose six most sensitive parameters of the drain‐source current model and the gate charge model. The statistical method is modeled by using a symbolic processing method to change the range of the six parameters. The statistical model is implemented in Agilent ADS software for validation. A S‐band GaN HEMT power amplifier is designed by using the established statistical model for demonstration purpose. The results show that good accuracy has been achieved by comparing measured and simulated output power (Pout) and power added efficiency (PAE). So it has been proven that this method is suitable for GaN HEMT power amplifier design and yield estimation. Copyright © 2016 John Wiley & Sons, Ltd.